ANALISA BANK DIGITAL TERHADAP BANK-BANK DI INDONESIA - Rati Rianti; Sinyo Alexander Dappa; Stansilaus Riesvaldo; Selvi Esther Suwu (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
The development of digital financial systems in Indonesia, driven by innovations such as QRIS and BI-FAST, has brought about significant changes in banking services. Digital banks have emerged as a solution offering convenience, speed, and flexibility in conducting financial transactions without the need to visit a branch. However, amidst this progress, there remains the challenge of low digital literacy among the public, which can hinder the optimal utilization of these services. Considering this, this journal discusses how the development and utilization of digital banking in Indonesia can provide convenient financial services for the public, including those with low levels of digital literacy. This study employs literature review method, collecting and analyzing various sources of scientific literature, such as journals and regulations relevant to digital banking. The analysis process was conducted systematically through the stages of data collection from journals, data reduction, interpretation, and synthesis to gain a comprehensive understanding of the phenomenon under study. The results of the study indicate that digital banks offer various conveniences, such as online account opening, real-time transactions, operational cost efficiency, and innovative features in financial management. In addition, digital banks also play a role in enhancing financial inclusion for those who have not yet been reached by banking services. However, there are challenges in the form of cyber security risks, potential data breaches, and low digital literacy, which increase vulnerability to online fraud. Therefore, there is a need to improve digital literacy, strengthen security systems, and ensure ongoing regulatory oversight.